Decision-making and the information system : Vol. 3 - Salles, Maryse (London : ISTE, 2015)
The purpose of this book is to question the relationships involved in decision making and the systems designed to support it: decision support systems (DSS). The focus is on how these systems are engineered; to stop and think about the questions to be asked throughout the engineering process and, in particular, about the impact designers' choices have on these systems.
Decision-Making / Maryse Salles -- Decision Support Systems / Maryse Salles -- The Influence of DSS on Decision-Making and Associated Risks / Maryse Salles -- Elements for Ethical DSS Design / Maryse Salles -- General Conclusion.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed July 15, 2015).
Keywords: COMPUTERS / Computer Literacy; COMPUTERS / Computer Science; COMPUTERS / Data Processing; COMPUTERS / Hardware / General; COMPUTERS / Information Technology; COMPUTERS / Machine Theory; COMPUTERS / Reference; Decision making; Statistical decision; Computer programming -- Decision making; Computer science; Decision making -- Mathematical models; Decision making; Statistical decision; Electronic books